Proof by Electronically Generated Evidence under the Evidence Act (2011) - Taanimu, Adamu Idris; Doma-Kutigi, Halima (ABUAD Law Journal, 2021)
The underlying principle upon which the concept of weight of evidence is based is that the court is urged to confer probative value or otherwise on a document that is being tendered and received in evidence.An invitation to ascribe probative value to a document which is evidence before the court works on the assumption that the document has been admitted in evidence as an exhibit. This assumption or presumption is rebuttable as the admissibility of a document could still be a relevant factor in the course of final addresses, judgment or even on appeal.Two key factors are critical in respect of electronic evidence in judicial trials or proceedings. These are admissibility and weight of documents. However, while the Evidence Act (2011) creates a general framework regarding the weight to be attached to such electronic evidence, it does not set out any basis for the opposing party to be able to show that the produced electronic evidence falls short of any of the above factors for probability. The challenges a party seeking to show that the produced electronic evidence is not probable are enormous. Implicit in the factor for admissibility is the confidentiality of the electronic evidence. Using doctrinal approach through content analysis of Nigerian statutes, case law, and relevant literature, the paper examines the principles relating to the ascription of probative value or weight of electronic evidence as a means of proof of a particular fact in judicial proceedings. The paper finds that generally, it is difficult to detect where the product of an electronic device has been tampered with; and since the provisions of the Evidence Act, 2011 is not clear on the authentication of electronic documents, the chance that the courts are more likely to be misled by evidence produced through an electronic device is higher than a hard copy of the evidence. Accordingly, the paper recommends that the Act be amended to include detailed rules for presenting electronically generated evidence.